New genotypes and molecular characterization of Enterocytozoon bieneusi in pet birds in Southwestern China. (December 2019) - Deng, Lei; Yue, Chan-Juan; Chai, Yi-Jun; Wang, Wu-You; Su, Xiao-Yan; Zhou, Zi-Yao; Wang, Long-Qiong; Li, Ling-Yu; Liu, Hai-Feng; Zhong, Zhi-Jun; Cao, Sui-Zhong; Hu, Yan-Chun; et al.
Abstract: Enterocytozoon bieneusi, a unicellular enteric microsporidian parasite, can infect humans and a wide range of animals throughout the world. Although E. bieneusi has been identified in many animals, there is no information regarding the genotypes of E. bieneusi in pet birds in China. Birds are important sources of emerging infectious diseases that affect humans, and immunosuppressed individuals can be exposed to potential zoonotic agents shed by birds. The aim of the present study was to determine the prevalence and genotypic diversity of E. bieneusi in pet birds, as well as assessed its zoonotic potential. A total of 387 fecal samples were collected from Psittaciformes (n = 295), Passeriformes (n = 67), and Galliformes (n = 16) from four pet markets in Sichuan province, Southwestern China. The overall prevalence of E. bieneusi in pet birds was 25.1% based on nested polymerase chain reaction analysis of the internal transcribed spacer (ITS) region of the ribosomal RNA (rRNA) gene (Psittaciformes, 21.7%; Passeriformes, 37.3%; Galliformes, 50.0%). Eight genotypes of E. bieneusi were identified, including five known genotypes (D, SC02, BEB6, CHB1, and MJ5) and three novel genotypes (SCB-I, SCB-II, and SCB-III). In phylogenetic analysis, genotypes D and SC02 and one novel genotype SCB-II were clustered within group 1, genotype BEB6 was classified within group 2, and the remaining genotypes (CHB1, MJ5, SCB-I, and SCB-III) clustered with group 10. To the best of our knowledge, this is the first report of E. bieneusi infection in pet birds in China. Genotypes D, SC02, and BEB6 that have been previously identified in humans, were found in pet birds in this study, suggesting that these pet birds can be a potential source of human microsporidiosis in China. Highlights: This is the first to report the prevalence of E. bieneusi in pet birds in China. The overall prevalence of E. bieneusi was 25.1% (97/387) based on PCR analysis of the ITS region of the ribosomal RNA gene. Five known genotypes (D, SC02, BEB6, CHB1, and MJ5) and three novel genotypes (SCB-I, SCB-II, and SCB-III) were identified. This study will enrich the epidemiological data of E. bieneusi infection in China.